Irisin level in response to the patients with metabolic impairments - Algul, S.; Ozcan, S.; Barutcu, A.; Serhatlioglu, I.; Berilgen, S.; Ozcelik, O. (Wiley-Blackwell, 2014)
[Abstract Not Available]
Keywords: Irisin; cerebrovascular disorders; myocardial infarction; pulmonary disease